Critical Synthesis Package: Leeds Attitude Towards Concordance II Scale (LATCon II) - David Way (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Leeds Attitude Towards Concordance Scale II (LATCon II), and (2) a copy of the LATCon II developed by Jill Thistlethwaite, PhD. The LATCon II is a 20-item instrument for measuring attitudes towards concordance, a patient care model that requires health care practitioners to understand and respect the patient's perspectives when making decisions about prescribing medications. Response options for all 20 items are presented as 4-point forced-choice Likert response sets tagged and scored from 0 (Strongly Disagree) to 3 (Strongly Agree). The best way to use this instrument is to score and sum all 20 items (after recoding negative items) and to use the resulting score as an index of attitude towards concordance. Higher scores on the LATCon II indicate a more positive attitude, while lower scores indicate a more negative attitude. The instrument has been translated into Spanish and used in Spain with psychiatrists, and has been adapted for use with allied health professions students in the United States. The LATCon II was demonstrated to have sufficient internal consistency and stability. Content validity was established through expert review of items during the development of the instrument.